Nanofluids Containing Electromagnetic Nanoparticles: The Review of Electrical Properties and Applications - Boiko, Oleksandr; Stryczewska, Henryka Danuta; Komarzyniec, Grzegorz Karol (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper presents a brief review of the electrical properties of nanofluids containing metallic, metallic oxide, graphene nanoparticles, as well as carbon nanotubes. The key factors, such as the alignment of magnetic nanoparticles (NPs), NPs size and shape, surfactants, temperature, base fluid, and NPs types, that demonstrate a significant impact on the electrical properties of nanofluids are analyzed. The applications of nanofluids in transformers (oil, cores, paper impregnation), PVT systems, and hydrogen production are described.